LPS-induced Src family kinases activity mediates IL-10 production through activation of STAT3 in peripheral blood mononuclear cells of patients with Behçet’s Disease - Irtegun Kandemir, S.; Tekin, M. A.; Bozkurt, M.; Dagli, A. Z.; Kalkanli-Tas, S. (Cellular and Molecular Biology, 2017)
Behçet’s disease (BD) is achronic inflammatory disorder characterized by recurrent oral and genital ulcers, uveitis and skin lesions. Although,the pathogenesis of BD remains poorly understood, excessive or dysregulatedcytokine production including IL-10 is associated with BD. Revealing the key molecular mechanism by which IL-10 expression is regulated is crucial to understanding the pathogenesis of BD. The aim of this study was to investigate whether Src family kinases (SFKs) are upstream mediators of STAT3/IL-10 pathway in peripheral blood mono nuclear cells(PBMCs) of active BD patients.Twenty active BD patients and twenty healthy subjects used as control were included in the study. PBMCs were isolated from total blood by density gradient centrifugation.Western blot and ELISA methods were applied to analyzelipopolysaccharide (LPS)-induced SFKs/STAT3/IL10 signaling pathway in BD.Inhibition of SFKs activity suppressed LPS-induced IL-10 production in PBMCs fromboth controls and active BD patients. Similarly, blockage of STAT3 activation abrogated LPS-induced IL-10 production. However, LPS-induced STAT3 activation required for IL-10 production was found to be dependent on SFKs activity as LPS-induced STAT3 phosphorylation was reduced by the inhibition of SFKs activity in PBMCs of active BD patients.SFKs activity is essential for LPS-induced STAT3/IL-10 pathway in PBMCs of active BD patients. Manipulation of the SFKs activity may offer a novel therapeutic approach for BD.